A, Masamba Lived experiences and pathways to unsafe abortion among women and adolescents accessing post abortion care at selected hospitals in Lilongwe, Malawi: An interpretive phenomenological study. - Anthony Masamba (International Journal of Health, 2024)
Every year, women and adolescents in the world seek abortion for unwanted pregnancies, with nearly half of these abortions being unsafe. Women and adolescents who suffer an unsafe abortion develop short and long-term complications. In Malawi, unsafe abortion is main cause of maternal deaths. At least 23% of all maternal deaths are due to complications of unsafe abortions. Aim: To explore lived experiences, pathways, facilitators and barriers to unsafe abortion among women and adolescents accessing post-abortion treatment at selected hospitals in Lilongwe, Malawi. Method: Phenomenological study design was used. Study population were women and adolescents who were receiving post abortion treatment at Bwaila Hospital and Kabudula Community Hospital respectively. 25 women who had unsafe abortion in the past four years were interviewed. Data was collected by in-depth and key informant interviews. Voice recorders were used. Verbatim was transcribed, translated into English and written in the note book. Atlas-Ti software version 8.0 was used for data analysis. Results: Pathways to unsafe abortions included power relations, lack of knowledge of PMTCT, infidelity and fear of divorce and child spacing and family size. Facilitators of safe abortion services were: village clinics, establishment of bylaws in the community, introduction of sexuality education in primary schools, promotion of sexual reproductive health mobile clinics among others. Whereas barriers to safe abortions included, social, cultural, religious, physical and attitude barriers. Lived experiences included: sterility, anger, excommunication from the church, divorce, social effects, disability, depression, loss of learning, nightmares, suicide attempts, near-death illnesses, denial and stigma. Conclusion: Increasing investment in post abortion care (PAC), creating awareness, and improve availability of sexual and reproductive health services can reduce the cases of unsafe abortion and its adverse consequences in Malawi and similar settings.